Integrated approaches for food, nutrition and livelihood security of rural households in Fatehpur district of Uttar Pradesh - Kumar, Rajesh; Nath, C P; Devraj, Devraj; Praharaj, C S; Tripathi, Chandra Mani; Kumar, Pradeep; Shivakant, Shivakant; Bhat, Shripad; Singh, N P; Chahal, V P (Indian Farming, 2022)
.